Analisis Social Return On Investment (SROI) Dalam Penerapan Program “Agroeduwisata Mamalam”. - Amelia, Thamya; Fermata, Wydia; Puspita Sari, Eka; Ayu, Kintan; Badriansyah, Bintang (Universitas Djuanda Bogor, 2024)
This research aims to measure the impact of implementing the Manak Mandiri Man Alam (Mamalam) Agro-tourism Program, which is a CSR initiative from PT ANTAM Tbk UBPB West Kalimantan. This program is designed to provide social responsibility to society and the environment through the integration of agricultural activities with education and tourism. The analysis was carried out using the Social Return on Investment (SROI) method to evaluate the resulting social, economic and environmental impacts. In this research, primary and secondary data were collected to evaluate program input, output and outcomes and quantify the resulting social value. The results of the SROI calculation show a ratio of 2.32, which means that every Rp. 1 invested by ANTAM in this program produces Rp. 2.32 in economic, social and environmental benefits. This SROI value confirms that the various activities that have been carried out have been well planned, targeting the right targets, and the targets to be achieved are linear with the planned activities. These findings demonstrate the success of the program in providing a significant positive impact on society. Apart from that, the results of this research also provide a valuable reference for the development of similar programs and strategic decision making for stakeholders, strengthening the argument for continuing to support initiatives oriented towards community empowerment and environmental preservation.